Accumulative Plastic Deformation of the Improved Completely Weathered Granite Subgrade in High-Speed Railway - Changzi Qu; Jing Zhao; Zheng Wang; Ze Liu; Ganghui Hou; Xiangxiang Zhou (Advances in Materials Science and Engineering)
The improvement and reuse of completely weathered granite (CWG) with poor engineering properties for backfilling embankments can help protect the environment and bring great economic benefits. The embankment of high-speed railways demands an extremely low additional subgrade settlement under long-term dynamic loads. To analyze the applicability of the improved CWG used for subgrade filling, a series of laboratory dynamic triaxial and field cyclic loading tests were carried out. On the basis of the test results, a calculation model of accumulative plastic strain considering the dynamic stress ratio and the cement content was established. Using the proposed model and the numerically calculated dynamic stress, the accumulative plastic deformation of an embankment filled with improved CWG under various driving conditions was calculated and discussed. The variation of accumulative plastic deformation of the improved CWG with loading cycles could be described by a power function. The dynamic stress level had a significant influence on the accumulative plastic strain, and the strain in the bottom layer of the subgrade bed was greatly attenuated. Accordingly, most of the accumulative plastic deformation attenuation occurred within the depth range of the subgrade bed. The final total accumulative plastic deformations of the embankment were less than 2 mm (5 mm for the limit value) after 4 million times of high-speed train loadings, proving that the improved CWG can be used for subgrade filling. The influence of the axle load on accumulative plastic deformation was more significant than that of the train speed. The proposed calculation model of the accumulative plastic strain could provide valuable reference for similar railway engineering.